Biosorption of heavy metal ions, oil and grease from industrial waste water by banana peel - Borhan, A. (Trans Tech Publications Ltd, 2014)
The objective of this research is to study the potential of using banana peel as a biosorbent in removing heavy metal ions (Cu2+, Zn2+ and Pb2+) and oil/grease particles from industrial waste water. The study emphasizes on the parameters involved in the preparation phase of the banana peel adsorbent, such as particle sizes, activating agent, impregnation ratio, carbonization temperature and duration. Based on the findings, it shows that the adsorption capacity is correlated to the total surface area (SBET), pore volume (VT) and average pore diameter (D) of the materials. Sample A20 yields the highest percentage removal for all tested waste water pollutants, suggesting that banana peel based activated carbon can be used effectively as biosorption material. Â© 2014 Trans Tech Publications, Switzerland.